Odpowiedzi

2010-03-30T15:22:55+02:00
1. Wykonaj mnożenie :
2(x+3)=2x+6
5(3x-1)=15x-5
(-4) x (2a-b)= -4x (2a-b) = -8ax +8bx
2. Wykonaj dzielenie :
a) (6x-2y) :2= (6x-2y) * 1/2 = 3x-y
b) (-3a - 1 1/2) : (-3)=(-3a - 3/2) * -1/3= a+ 1/2
2010-03-30T15:23:29+02:00
2(x+3)= 2x+6

5(3x-1)= 15x-5

(-4) x (2a-b)=-8a+4b

a) (6x-2y) :2=3x-y

b) (-3a - 1 1/2) : (-3)=a+(³/₂*(-⅓))=a-½
2010-03-30T15:23:47+02:00
2(x+3)=2x+6
5(3x-1)=15x-5
(-4)x(2a-b)=-4x(2a-b)=-8xa+4xb
(6x-2y):2=3x-y
(-3a-1 1/2):(-3)=a+1/2

Myślę, że pomogłam ;)
Pozdrawiam.